Planetary astronomy : from ancient times to the third millennium - Schorn, Ronald A. (Ronald Anthony), 1935- (Texas A & M University Press, 1998)
In Planetary Astronomy: From Ancient Times to the Third Millennium, Ronald A. Schorn shows how times, ways of thinking, and planetary astronomy itself have changed over the millennia. Schorn presents a firsthand account of the triumphs, tragedies, and fiascos in the field. He covers why the science "fell from grace," presenting both the nonplanetary astronomers' and planetary astronomers' viewpoints. Drawing on hundreds of interviews, direct observation, and extensive documentation to render events with a sense of immediacy and reality, he gives the reader an idea of what situations were like when no one knew the answers.